Smartphone based automatic price determination of agricultural products - Hassan, Md Rakib (Research in Agriculture Livestock and Fisheries, 2017)
Smartphones are increasingly becoming an integral part of our life. We carry it every time with us and use it to do various tasks including browsing internet, emails, social websites and others. We also perform online shopping with our smartphones. In this paper, a new automatic price determination algorithm for agricultural products is proposed that can be used by both the sellers and buyers using their smartphones. The buyers will place their demands for their required agricultural products to the sellers of a particular market and the sellers will also place their supplies. The algorithm will then automatically calculate the market equilibrium price using learning rate based iterative distributed price determination algorithm. As a result, both the sellers and buyers can save their time in finding the suitable prices of the agricultural products. The performance results show that the algorithm is stable and reaches the market equilibrium price within a few milliseconds. Res. Agric., Livest. Fish.4(2): 69-75, August 2017